2019
DOI: 10.1158/1078-0432.ccr-18-2752
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Multiple Myeloma with AMG 424, a Novel Anti-CD38/CD3 Bispecific T-cell–recruiting Antibody Optimized for Cytotoxicity and Cytokine Release

Abstract: Purpose: Despite advances in the treatment of multiple myeloma, new therapies are needed to induce more profound clinical responses. T-cell-redirected lysis triggered by bispecific antibodies recruiting T cells to cancer cells is a clinically validated mechanism of action against hematologic malignancies and CD38 is a tumor-associated antigen with near-universal expression in multiple myeloma. Thus, an anti-CD38/CD3 bispecific T-cell-recruiting antibody has the potential to be an effective new therapeutic for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 46 publications
2
69
0
Order By: Relevance
“…Importantly, in the context of human IgG heterodimeric bispecific antibodies, F2 family members retained full efficacy against cancer target cells while demonstrating low levels of cytokine release (30). Consistent with our results, recent studies by Zuch de Zafra et al (31) and Li et al (32) also demonstrated that T-cell mediated cytotoxicity can be decoupled from cytokine release when using TCEs. Li et al further showed that initial release of TNF from T-cells was the primary culprit driving CRS by triggering downstream proinflammatory cytokine release from monocytes.…”
Section: The Next Generation Of T-cell Engagerssupporting
confidence: 91%
“…Importantly, in the context of human IgG heterodimeric bispecific antibodies, F2 family members retained full efficacy against cancer target cells while demonstrating low levels of cytokine release (30). Consistent with our results, recent studies by Zuch de Zafra et al (31) and Li et al (32) also demonstrated that T-cell mediated cytotoxicity can be decoupled from cytokine release when using TCEs. Li et al further showed that initial release of TNF from T-cells was the primary culprit driving CRS by triggering downstream proinflammatory cytokine release from monocytes.…”
Section: The Next Generation Of T-cell Engagerssupporting
confidence: 91%
“…AMG424, a BiTE targeting CD38, has also been reported to show potent activity against MM cell lines, with both low and high CD38 expression in vitro [121]. This agent also inhibited tumor growth in murine models and showed acceptable toxicity in monkeys.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…This agent also inhibited tumor growth in murine models and showed acceptable toxicity in monkeys. The expression of CD38 on NK cells, monocytes and a subset of B cells raises the question of the impact of this therapy on other immune effector cells [121,122]. Zuch de Zafra et al showed that although therapeutic doses of AMG424 resulted in B cell depletion, significantly higher doses were required to affect NK cell, monocytes and T-cells [121].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Anti-CD38/CD3 bispecific antibodies have not yet been clinically developed but have the potential to become curative options for multiple myeloma and other lymphoid malignancies, given the widespread expression of CD38 on malignant cells. Zuch de Zafra and coworkers have recently demonstrated considerable in vitro and in vivo activity of the novel anti-CD38/CD3 bispecific antibody AMG 424 against high and low CD38-expressing cells, such as those previously exposed to Daratumumab [107]. Clinical trials assessing the activity of such therapy in r/r MM are currently recruiting patients (NCT03309111, clinicaltrials.gov), and optimal results may extend their use to other lymphoid malignancies.…”
Section: Cd38 In the Era Of Immunotherapy And Cellular Therapymentioning
confidence: 99%